Uterine tamponade using condom catheter balloon in the management of non-traumatic postpartum hemorrhage - Jain, Renu (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2018)
Background: In low-resource countries, Postpartum Hemorrhage (PPH) is the leading cause of maternal mortality. The intrauterine balloon tamponade was recently incorporated into the strategy to manage uterine atony. There are many types of tamponades. Among them, the condom catheter seems to be an efficient and economic intervention for the treatment of PPH in low-resource countries. The aim of present study was to evaluate the effectiveness of the condom catheter balloon in treating postpartum hemorrhage refractory to medical treatment. Methods: The retrospective analysis of 22 cases of PPH, treated with a condom catheter as a conservative therapeutic option, was done in department of Obstetrics and Gynaecology, Gajra Raja Medical College, Gwalior, Madhya Pradesh, India. Results: The condom catheter was successful in controlling PPH in 90.9% cases. It was effective in 94.44% women with uterine atony, who did not respond to uterotonic drugs. It was also effective in one case of placental implantation site bleeding and two cases of deranged coagulation function. In 2 cases it failed to control PPH and peripartum hysterectomy was done. The volume of saline solution used to fill the balloon was from 150 -350 ml and the time for which the balloon remained inflated was 36-48 hours. No case of febrile morbidity and wound sepsis was noted. There was no maternal death. Conclusions: Its ease of use and high effectiveness make condom catheter a useful approach for the conservative management of PPH. This device reduces bleeding, shortens the hospital stay and avoids the need for more aggressive procedures.